Elements of the potato plant protection system against alternaria blight for cultivation on the basis of organic farming in the Polissya zone of Ukraine - Taktaiev, B.; Podberezko, I.; Furdyga, M.; Oliinyk, T.; Nikishycheva, K. (Quarantine and plant protection, 2025)
Goal. To develop elements of biological protection of potatoes against alternaria blight under biological farming conditions in order to obtain environmentally safe products. Methods. Field, laboratory, and statistical methods. Results. In 2021—2023, research was conducted at the Institute for Potato Research based on a stationary experiment within a four-field crop rotation system with potatoes as the main crop, on sod-podzolic sandy loam soils typical for the Polissya zone of Ukraine. The study focused on the effectiveness of plant protection elements for the potato variety Myroslava against alternaria blight. The developed protection elements included combinations of biofungicides with biologically active substances (BAS), organic and organo-mineral fertilizers. The technical effectiveness of the plant protection elements against alternaria blight in the experimental treatments ranged from 55.3% to 71.9%. The protection level provided by MycoHelp, R (antagonistic fungi of the genus Trichoderma (T. viride, T. ligmorum), live cells of Bacillus subtilis, Azotobacter, Enterobacter, Enterococcus, with a total viable cell count of not less than 1.0 × 10⁹ CFU/ cm³) and Bactofit, WP (Bacillus subtilis, strain IPM 215, 10,000 ED/g, titer not less than 2 billion spores/g) against the background of double green manure fallow + ColoradoCid, WP (Bacillus thuringiensis ssp. thuringiensis, titer not less than 2 billion spores/g) was higher compared to Phytodoctor, WP (live cells and spores of Bacillus subtilis, improved strain BS 323, titer not less than 5 × 10⁹ CFU/ml). The highest efficiency levels — 71.6% and 71.9% — were achieved through combined protection (background + tuber treatment + three foliar treatments), both for MycoHelp and Bactofit. This level of protection resulted in yields of 38.8 and 44.0 t/ha, which exceeded the control (20.0 t/ha) by 18.8 and 24.0 t/ ha, respectively. Conclusions. Over the years of research, it was established that the efficiency of potato cultivation depends on both the fertilization system and the elements of crop protection, as an effective protection system is a prerequisite for reducing yield losses during the growing season and during the storage of potato tubers. The use of biofungicides and their combinations with BAS, organic and organo-mineral fertilizers has a significant impact on the level of protection against alternaria blight and on potato yield.